In vitro and in vivo evaluation of antifungal combinations against azole-resistant Aspergillus fumigatus isolates - Jemel, Sana; Raveloarisaona, Yannick; Bidaud, Anne-Laure; Djenontin, Elie; Kallel, Aicha; Guillot, Jacques; Kallel, Kalthoum; Botterel, Françoise; Dannaoui, Eric (Frontiers in Cellular and Infection Microbiology, 2023)
Azole resistance in Aspergillus fumigatus (Af) has become a widespread threat and a major concern for optimal management of patients with invasive aspergillosis (IA). Combination of echinocandins with azoles is an attractive alternative option for the treatment of IA due to azole-resistant Af strains. The aim of this study was to evaluate the in vitro and in vivo combination of caspofungin (CAS) with either voriconazole (VRZ) or posaconazole (PSZ). In vitro interactions were assessed by two methods, and an animal model of IA in Galleria mellonella was used for in vivo evaluation. Assessment of efficacy was based on larvae mortality. Groups of 10 larvae were infected by 3 clinical strains of Af (azole susceptible, AfS; PSZ resistant, AfR1; VRZ and PSZ resistant strain, AfR2). In vitro, combination of CAS and azoles was indifferent against AfS, and AfR2, and a synergy was found for AfR1. When compared to VRZ monotherapy, the combination of VRZ at 4 µg/larva with CAS at 4 µg/larva improved survival of AfR2-infected larvae (p=0.0066). Combination of PSZ at 4µg/larva with CAS at 4 µg/larva improved survival of AfR1-infected larvae compared to CAS (p=0.0002) and PSZ (0.0024) monotherapy. Antagonism was never observed. In conclusion, the combination of caspofungin with azoles is a promising alternative for the treatment of azole resistant strains of Af.